Effective Electron Density Distributions Describing VLF/LF Propagation Data - Morfitt, D G (1977)
This report presents vlf/lf field strength measurements obtained between 9 and 60 kHz for several radio propagation paths. These include several radials outward from Hawaii, several transmission paths across the continental United States, and high latitude propagation over the Greenland Ice Cap. Effective exponential electron density profiles are derived yielding predicted signal levels that simulate the experimental data.